ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ СПОСОБІВ І ПОРЯДКУ ПОСТАЧАННЯ НАФТИ - Cherednikova, T.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2012)
The paper focuses on the relations on Ukraine’s oil market. The features and main problems concerning the legal regulation of social relations arising in the process of oil supplies are examined, and legal ways and order of oil supplies are analysed. The proposals have been worked out to improve the legal regulation of given relations in order to provide an effective organization of oil supply market in Ukraine.